2016
DOI: 10.5194/acp-16-14357-2016
|View full text |Cite
|
Sign up to set email alerts
|

First detection of ammonia (NH<sub>3</sub>) in the Asian summer monsoon upper troposphere

Abstract: Abstract. Ammonia (NH 3 ) has been detected in the upper troposphere by the analysis of averaged MIPAS (Michelson Interferometer for Passive Atmospheric Sounding) infrared limb-emission spectra. We have found enhanced amounts of NH 3 within the region of the Asian summer monsoon at 12-15 km altitude. Three-monthly, 10 • longitude × 10 • latitude average profiles reaching maximum mixing ratios of around 30 pptv in this altitude range have been retrieved, with a vertical resolution of 3-8 km and estimated errors… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
68
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 77 publications
9
68
0
1
Order By: Relevance
“…In a new finding, the model indicates the presence of gas‐phase ammonia, preferentially on the northern flank of the ASM anticyclone. This provides evidence to support spectral measurements made from the MIPAS satellite and aircraft limb IR measurements during the StratoClim campaign (Höpfner et al, , ). Backscatter estimates diagnosed from the model simulation are low compared with those obtained from CALIPSO observations.…”
Section: Discussionsupporting
confidence: 84%
“…In a new finding, the model indicates the presence of gas‐phase ammonia, preferentially on the northern flank of the ASM anticyclone. This provides evidence to support spectral measurements made from the MIPAS satellite and aircraft limb IR measurements during the StratoClim campaign (Höpfner et al, , ). Backscatter estimates diagnosed from the model simulation are low compared with those obtained from CALIPSO observations.…”
Section: Discussionsupporting
confidence: 84%
“…, ]. Seasonal enhancements observed in several trace gases and aerosols have indicated such trapping of polluted air masses [ Li et al , ; Fu et al , ; Park et al , , ; Funke et al , ; Glatthor et al , , ; Xiong et al , ; Randel et al , ; Schuck et al , ; Baker et al , ; Vernier et al , , ; Fadnavis et al , ; Umezawa et al , ; Barret et al , ; Chirkov et al , ; Gu et al , ; Höpfner et al , ; Ungermann et al , ].…”
Section: Background Motivation and Contextmentioning
confidence: 99%
“…Ammonia is a significant trace gas and is a subject of studies of different remote‐sensing missions (e.g., Beer et al, ; Höpfner et al, ). Experimental studies under Jovian conditions (Devaraj et al, ) suggested that broadening of ammonia lines by water can make an important difference when interpreting spectra from gas giants.…”
Section: Generated Data Setsmentioning
confidence: 99%
“…Ammonia is a significant trace gas and is a subject of studies of different remote-sensing missions (e.g., Beer et al, 2008;Höpfner et al, 2016).…”
Section: Nhmentioning
confidence: 99%